(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Intraventricular hemorrhage (IVH) remains a serious complication in preterm infants, particularly those born with low birth weight or reduced gestational age. It is a major contributor to neonatal illness and death, especially in resource-limited regions such as Pakistan, where information on its prevalence and contributing factors is still scarce. Objective: To determine the incidence of IVH in preterm newborns admitted to Sir Ganga Ram Hospital, Lahore Methods: This prospective observational cross-sectional study was conducted at the Department of Pediatrics, Sir Ganga Ram Hospital from 15 September 2024 to 15 March 2025. A total of 81 preterm neonates (aged 0–28 days) were enrolled through non-probability consecutive sampling. Cranial ultrasounds were performed within the first week of life and reported by a consultant radiologist. Data were analyzed using SPSS v20.0 with stratification and chi-square tests. Results: The overall incidence of IVH was 25.9%. A significantly higher incidence was observed among neonates <30 weeks gestation (60%) and those with birth weight <1.5 kg (58.8%) (p < 0.05). Gestational age and birth weight were strong predictors of IVH risk. Conclusion: IVH remains a prevalent complication in preterm neonates, with highest risk among those born extremely premature and with very low birth weight. These findings emphasize the need for early neuroimaging, enhanced prenatal care, and targeted preventive strategies in high-risk neonates. Local hospital-based data are essential to improve neonatal outcomes and formulate evidence-based protocols in tertiary care settings.